Self‐management of immunomodulatory drug treatment in multiple myeloma patients. (6th November 2020) - Cransac, Amélie; Aho, Serge; Cosme, Edouard; Chretien, Marie‐Lorraine; Favennec, Camille; Schreder, Laure; Boutet, Mérédith; Gueneau, Pauline; Giroud, Maurice; Caillot, Denis; Boulin, Mathieu
Abstract: Objective: Immunomodulatory drugs (IMIDs: thalidomide, lenalidomide and pomalidomide) are widely used in patients with multiple myeloma (MM). The aim of our study was to validate a questionnaire to evaluate the self‐capacity of MM patients to manage IMID treatment including side effects. Methods: We used a method adapted from the recommendations of the European Organisation for Research and Treatment of Cancer (EORTC) to validate a French questionnaire for patients with MM treated with IMIDs. Results: The face validity was evaluated in 15 patients and the construct validity in 56 patients. For discriminant validity, two groups were constituted by gender and depending on whether they had a previous IMID treatment. The median questionnaire score was 11.33/16 (IQR 9.75‐12.08) with a minimum of 5.2 and a maximum of 14.75. For discriminant validity, a statistically significant difference was observed for patient capacity to contact healthcare professionals in specific situations and drug intake in case of swallowing disorder. Convergent validity showed an acceptable reliability for the scores of the different questions. Conclusion: The questionnaire has shown to be a valid tool for the assessment of the adherence and side‐effect management skills for MM patients with IMID treatment.